A local structural derivative PDE model for ultraslow creep. (1st October 2018) - Yang, Xu; Liang, Yingjie; Chen, Wen
Abstract: In this short communication, an ultraslow creep PDE model is proposed via the local structural derivative. The inverse Mittag-Leffler (ML) function is selected as the structural function which is capable of characterizing ultraslow creep. The data on the Ultra-High Performance Concrete (UHPC) are tested to examine the proposed PDE model. The results indicate that the proposed PDE model has better usability and higher accuracy compared with the traditional Kelvin model, where the parameter γ reflects the pore content in different time scales. The structural derivative model can be considered a potential modeling methodology to describe challenging ultraslow creep problem.